Prophetic Learning Methods for Strengthening Islamic Education in Society 5.0 - Bagus Jamroji; Arif Fathul Uluma (Immortalis Journal of Interdisciplinary Studies, 2026)
The rapid development of digital technology in the Society 5.0 era presents both opportunities and challenges for Islamic Religious Education (PAI). While technology enables adaptive and personalized learning, it may also contribute to moral degradation, superficial spirituality, and the weakening of humanistic values. This study aims to analyze the relevance of Prophetic Learning Methods in strengthening Islamic Religious Education in the Society 5.0 era and to formulate strategies for integrating prophetic values into contemporary educational practices. Using a qualitative approach based on library research, the study examines various educational methods employed by the Prophet Muhammad SAW.  The findings reveal that Prophetic Learning Methods, including exemplary behavior (uswah), empathetic dialogue (hiwar), habituation (ta'wid), direct practice, problem-solving, gradual instruction (tadarruj), and persuasive advice (mau'izhah hasanah) embody humanistic, holistic, and transformative characteristics. These methods align with the human-centered educational paradigm of Society 5.0, which places human development at the center of technological advancement. Integrating Prophetic Learning Methods into Islamic Religious Education can enhance character formation, spiritual intelligence, and ethical digital literacy. Therefore, Islamic Religious Education should not be dominated by a technocentric approach but should remain a key medium for nurturing moral values. In this context, prophetic values serve as the foundation, technology functions as a tool, and Islamic Religious Education acts as a medium for internalizing values in response to contemporary educational transformation.